A distinct strain of tomato leaf curl New Delhi virus that causes mosaic disease in ash gourd and other cucurbitaceous crops - Vignesh, S.; Renukadevi, P.; Nagendran, K.; Senthil, N.; Kumar, R. Vinoth; SwarnaPriya, R.; Behera, Tusar Kanti; Karthikeyan, G. (Frontiers in Microbiology, 2023)
Ash gourd (Benincasa hispida) is a cucurbitaceous crop cultivated for its edible vegetable rich in vitamins, minerals, dietary fibres and antioxidants. In a field survey conducted in the Udumalpet region of Tamil Nadu during 2019, an incidence of 75 per cent mosaic disease on ash gourd crop was observed. DNA-A and DNA-B components of begomovirus genome were identified with this disease. Both the cloned DNA-A and DNA-B genomic components shared a highest pairwise sequence identities with the isolates of tomato leaf curl New Delhi virus (ToLCNDV), a bipartite begomovirus. Recombinant analysis showed both the components are possibly evolved through intra-species recombination between ToLCNDV isolates. Tomato leaf curl Bangladesh betasatellite (ToLCBB) is not naturally associated with this sample. The results of infectivity studies on ash gourd and other cucurbitaceous crops demonstrates the Koch's postulates, when co-inoculation of DNA-A and DNA-B of ToLCNDV was done. However, the inoculation of non-cognate ToLCBB along with DNA-A and DNA-B enhances the symptom expression and reduces the time taken for symptom development. Thus, Koch's postulates were proved for these virus complexes on cucurbitaceous crops. Further, an enhanced accumulation of DNA-A component was detected in the cucurbits co-inoculated with ToLCNDV and ToLCBB. This report highlights the importance of investigating the spread of these disease complexes with other cucurbitaceous crops in India.